A simple and sensitive HPLC-UV method for the quantification of piceatannol analog trans-3,5,3′,4′-tetramethoxystilbene in rat plasma and its application for a pre-clinical pharmacokinetic study - Lin, H.-S. (2014)
10.1016/j.jpba.2009.09.024